Utilization of Chitosan as an Animal Feed Supplement and Its Effect on Fattening of Organic Rooste (Gallus domestica sp) - Firdamayanti Firdamayanti; Suherman Suherman; Minarni Rama Jura (Universitas Tadulako, 2019)
Chitosan has functional groups of an amine group (-NH2) that acts as a coagulant dyestuff, a protein binder, and an amino acid; and a hydroxyl group (-OH). The present of these functional groups cause high chemical reactivity of chitosan. Chitosan can be used as a dietary supplement of rooster. This study aimed to determine the effect of chitosan as a dietary supplement on fattening rooster. Fattening rooster can be seen from an increase of weight per week. This study provided bran as much as 200 gr/animal/day, then the bran was added with chitosan solutions as each concentration. The results obtained for the chicken A which given bran with chitosan solution increased in body weight of 0.1 kg at the first week, while for the chicken given bran without chitosan increased in body weight of 0.1 kg at the third week. For the chicken B which given bran with chitosan increased in body weight of 0.1 kg at the first week, while for the chicken given bran without chitosan increased in body weight of 0.1 kg at the second week. Based on the data for ± 1 months of study obtained that good chitosan concentrations used in this study for the chicken A were at concentrations of 6% and 8% by increasing each of 0.5 kg, while for the chicken B was at a concentration of 6% by increasing of 0.6 kg.